Substrate mediated interaction of terbium(iii) double-deckers with the TiO2(110) surface. Issue 21 (20th May 2021) - Serrano, Giulia; Sorrentino, Andrea Luigi; Poggini, Lorenzo; Cortigiani, Brunetto; Goletti, Claudio; Sessoli, Roberta; Mannini, Matteo
Abstract : STM and XPS characterization studies were used to deeply investigate the chemical environment of TbPc2 molecules on the TiO2 rutile surface, probing a strong interfacial interaction independently from surface preparation. Abstract : A terbium(iii )-bis(phthalocyaninato) neutral complex was deposited on the rutile TiO2 (110) surface, and their interaction was studied by Scanning Tunneling Microscopy (STM) and X-ray Photoelectron Spectroscopy (XPS). It was found that the TiO2 rutile surface favours the adsorption of isolated molecules adopting a lying down configuration with the phthalocyanine planes tilted by about 30° when they lie in the first layer. The electronic and chemical properties of the molecules on the surface were studied by XPS as a function of the TiO2 (110) substrate preparation. This study evidences that strong molecule–substrate interactions are present and a charge transfer process occurs from the molecule to the surface.